Starting from Scratch: Experiences from Developing the First Vascular Anastomotic Training Program in North Macedonia Using the Porcine Thigh as a Simulation Model - Eleonora O.F. Dimovska; Gordana Georgieva; Blagoja Srbov; Boro Dzonov; Goran Stevanovski; Sofija Pejkova (Archives of Plastic Surgery)
Microsurgical reconstruction constitutes a fundamental part of plastic and reconstructive surgery. It demands high dexterity and intricate technical skills. Its steep learning curve benefits from thorough training throughout residency, where using realistic simulation models in the appropriate sequence of complexity progression is essential in ensuring patient safety prior to progressing to a clinical setting. Commencing training on microvascular-like small diameter vessels could prove unsuitable and ineffective for inexperienced surgeons, however, the larger diameter neurovascular structures in the porcine thigh can provide excellent anastomotic training without compromising the animal tissue training sought after by residents. We present the results from implementing the first vascular anastomotic course in our country, where reconstructive theory was combined with simulated anastomotic training on the porcine thigh. Junior plastic surgery residents described acquiring comprehensive knowledge of reconstructive techniques and could successfully complete anastomoses, despite none to minimal previous experience. Using the porcine thigh should be encouraged as a start-up vascular anastomotic training tool as it provides realistic conditions and tissue handling training, and could improve quality of further training on microvascular structures.